2006
DOI: 10.1103/physreve.73.011302
|View full text |Cite
|
Sign up to set email alerts
|

Granular convection driven by shearing inertial forces

Abstract: Convection velocity measurements in vertically vibrated granular materials are presented. The convection velocity close to the walls grows quadratically with the difference between the maximum and critical, or excess, amplitude (proposed as a dynamic parameter to describe related problems) and it is shown numerically that the average bed-bottom relative velocity during the distancing between them, grows linearly with the squared as well. This is interpreted as the signature of an inertial shearing force or mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…(18)], critical V is equivalent to critical S and is also similar to our high-frequency limit. On the other hand, there have been experiments [29] at St ∼ 420 which showed a suppression of granular motions at frequencies <12 Hz, which may be similar to our lowfrequency limit. However, all of these experiments are at St 1, which differs from the St of our experiments.…”
Section: E Comparison With Previous Experimentssupporting
confidence: 87%
“…(18)], critical V is equivalent to critical S and is also similar to our high-frequency limit. On the other hand, there have been experiments [29] at St ∼ 420 which showed a suppression of granular motions at frequencies <12 Hz, which may be similar to our lowfrequency limit. However, all of these experiments are at St 1, which differs from the St of our experiments.…”
Section: E Comparison With Previous Experimentssupporting
confidence: 87%
“…Available data for the convection velocity at the walls, which show an exponent in Eq. 1 between 1 and 2 [6,11], cannot directly be compared to our data as Hejmady et al [9] showed that the exponent for the near-wall velocity is close to unity, while the rise velocity (as derived from their rise times) possesses a much steeper dependence on excitation acceleration.…”
mentioning
confidence: 67%
“…With this mechanism, a collective motion of the medium can transport larger particles to the top, which come to rest there if the downward flow zone is too small to be entered by these particles. This effect has been studied experimentally [2][3][4][5][6][7][8][9][10][11] and theoretically [12][13][14][15], while the focus of the article at hand is on the extrapolation of the Brazil nut problem to reduced gravity conditions found on small Solar System bodies. The Brazil nut effect has been, for example, made responsible for observed surface structures on small asteroids [16,17].…”
mentioning
confidence: 99%
“…This secondary flow is considered key for important practical processes such as segregation [5]. The wealth of experimental evidence demonstrating that convective flows can occur in a granular material [e.g., [6][7][8][9] has led to significant theoretical effort, with a number of proposed mechanisms for granular convection [e.g., 6,[10][11][12][13].…”
mentioning
confidence: 99%